Usage of Holt-Winters Model and Multilayer Perceptron in Network Traffic Modelling and Anomaly Detection - Szmit, Maciej; Szmit, Anna; Adamus, Sławomir; Bugała, Sebastian (Informatica)
Usage of Holt-Winters Model and Multilayer Perceptron in Network Traffic Modelling and Anomaly Detection